Prevalence Of Microbial Contamination In Cellulose Products Supplied In The City Of Tehran - Mohammad Mehdi Soltan Dallal; Fatemeh Hedayati Rad; Abbas Rahimi Forushani; Hamid Emadi Koochak; Shabnam Haghighat Khajavi; Ali Taheri Mirghaed; Hamid Choobineh; Mohammad Kazem Sharifi Yazdi (Tehran University of Medical Sciences, 2014)
Background and Aim: Along with the constant increase in world population and consequently, the growing need to provide cellulose, as the most abundant organic substance in nature to produce cellulose products, concerns regarding the possible contamination of these products might cause skin, and genital and urinary infections. The aim of this study is to determine the possible microbial contamination of these products supplied in the city of Tehran. Materials and Methods: This is a descriptive study on 200 samples of unexpired cellulose products including napkins, nappies, sanitary napkin, and cardboard boxes to carry sweets. Fifty samples were obtained in the city of Tehran during six months from September 2011 to February 2012. Microbial contamination was investigated according to the procedure proposed by the Institute of Standards and Industrial Research of Iran. Results: The results obtained indicate that 18 samples (9%) exceeded the level allowed for aerobic bacteria and molds in one gram of specimens. Besides, 16 samples (8%) were contaminated with at least one of the following bacteria: Streptococcus Group D, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli. A total of 34 samples (17%) could not be consumed. The least and the most contaminated products were sanitary napkins (0.5%) and cardboard boxes to carry sweets (5%), respectively. Conclusion: The presence of pathogenic bacteria in cellulose products that could cause skin, and genital and urinary tract infections asks for more control over such sanitary products.